Educational Management and Quality in Technological Training of a Public Higher Institute - Saravia, Giuliana (2022)
The socioeconomic changes that are taking place require excellent educational management and the creation of better conditions in the teaching of higher technical education. The purpose of the study is to determine the relationship between educational management and the quality of services offered in a public technological institution. From the methodological point of view, the research assumes a quantitative, descriptive, cross-sectional approach, with a non-experimental design. The study group was represented by 100 subjects. The results show a correlation level of r= 0.805, which indicates that the level of educational management corresponds to the quality offered in technical education. It is concluded that there is a significant relationship between the study variables corresponding to the Institute of Higher Technical Education.